Factors Affecting the Achievement of Rotary Club Management in Thailand from the Executive's Perspective - Laorujiralai, Rattanaporn (Asian Administration and Management Review, 2019)
The objectives of the study on the factors affecting the Achievement of Rotary Club Management in Thailand from the Executive's Perspective are to study the Rotary Club Management in Thailand and to study the internal factors affecting the Achievement of Rotary Club Management in Thailand from the executives of members of Rotary Club in Thailand in 4 regions for 257 clubs from 334 clubs calculated as 76.9%. The questionnaires are used as the tools in researching and analyzing with the statistical methods using the descriptive statistics which are frequency, percentage, mean, and standard deviation. The hypothesis is tested by using the inferential statistics which are Pearson's correlation coefficient and multiple regression analysis with the statistical significance at level.05. The research results reveal that the executives of most studied Rotary Clubs in Thailand have the opinions on the internal factors used by the organization in the management of Rotary Clubs in Thailand are overall in the medium level ( x =3.39). They have the opinions on the Achievement of Rotary Club Management in Thailand overall in the medium level ( x =3.71). From analyzing the internal factor elements in the organization by using the multiple regression analysis, it is found that the elements of internal factors positively affecting the Achievement of Rotary Club Management in Thailand with the statistical significance at level. 05 who are personnel, strategies of the organization, values, and culture of the organizations.